Opioid antagonists to prevent olanzapine-induced weight gain: A systematic review - S. Andrea Laguado, PharmD, BCPS, BCPP; Stephen R. Saklad, PharmD, BCPP (American Association of Psychiatric Pharmacists, 2023)
Introduction: Olanzapine (OLZ) is a second generation antipsychotic that is approved for the treatment of schizophrenia, bipolar disorder type 1 as monotherapy (acute manic or mixed episodes, maintenance), or as an add-on to lithium or valproate (manic or mixed episodes). It is one of the most effective antipsychotics for the treatment of schizophrenia, but concerns remain due to its significant metabolic adverse effects. Notably, OLZ has one of the highest rates of weight gain among all antipsychotic drugs. Previous studies report on potential mitigation of weight gain with opioid antagonists. A systematic review was conducted to summarize the impact of these agents on weight and BMI when used as adjuncts to OLZ. Methods: A systematic review of randomized controlled trials was conducted with 3 searches between March 2, 2021 and March 27, 2022. Results: Six studies met inclusion criteria, 5 of which assessed OLZ and samidorphan (SAM) and 1 of which assessed OLZ and naltrexone compared with OLZ monotherapy. A total of 1752 patients were included with 952 receiving SAM and 14 receiving naltrexone as an adjunct to OLZ. SAM was shown to mitigate OLZ-induced weight gain by 1.0 kg. Only 1 study assessed naltrexone with no statistically significant results for weight gain. Discussion: SAM is effective at reducing OLZ-induced weight gain. Naltrexone did not reduce OLZ-induced increases in weight or BMI. However, there is a paucity of data on other opioid antagonists as adjuncts to OLZ treatment to prevent increases in weight or BMI.